2010
DOI: 10.1111/j.1365-2966.2010.16727.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Excess sources: Compton thick QSOs, low-luminosity Seyferts or starbursts?

Abstract: We explore the nature of Infrared Excess sources (IRX), which are proposed as candidates for luminous [LX(2–10  keV) > 1043  erg   s−1] Compton thick (NH > 2 × 1024  cm−2) QSOs at z≈ 2. Lower redshift, z≈ 1, analogues of the distant IRX population are identified by first redshifting to z= 2 the spectral energy distributions (SEDs) of all sources with secure spectroscopic redshifts in the AEGIS (6488) and the GOODS‐North (1784) surveys and then selecting those that qualify as IRX sources at that redshift. A tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 80 publications
9
41
0
Order By: Relevance
“…Their SEDs are consistent with starburst activity showing no evidence for a hot dust component. Georgakakis et al (2010) conclude that there is little evidence for the presence of a large fraction of luminous Compton-thick sources in either the X-ray-detected or undetected population of DOG analogues. As far as the Xray detections are concerned, our findings are not that discrepant quantitatively, given that our fraction of Compton-thick sources is 4/12 among the brightest sources.…”
Section: Overall Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Their SEDs are consistent with starburst activity showing no evidence for a hot dust component. Georgakakis et al (2010) conclude that there is little evidence for the presence of a large fraction of luminous Compton-thick sources in either the X-ray-detected or undetected population of DOG analogues. As far as the Xray detections are concerned, our findings are not that discrepant quantitatively, given that our fraction of Compton-thick sources is 4/12 among the brightest sources.…”
Section: Overall Propertiesmentioning
confidence: 98%
“…The former have an X-ray to mid-IR luminosity ratio of L 2−10 keV /L 6 μm ≈ −1.3 (median), while the latter have L 2−10 keV /L 6 μm ≈ −3 (see Fig. 2 of Georgakakis et al 2010). This could imply that the samples of undetected DOGs indeed contain a large fraction of Comptonthick sources.…”
Section: Comparison With X-ray-undetected Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another widely applied mid-IR method for the selection of Compton-thick AGN ) relies on low X-ray to IR ratios. The principle behind this method is that a low L X /L IR ratio is a sign of heavy obscuration (but see Yaqoob & Murphy 2011;Georgakakis et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the lack of X-ray spectroscopy the fraction of Compton-thick sources cannot be readily quantified. Based on brighter sources with X-ray spectroscopy in the GOODS (Georgantopoulos et al 2011), AEGIS (Georgakakis et al 2010) and SWIRE fields (Lanzuisi et al 2009), the fractions of Compton-thick sources found among IR-excess AGN range between 0% and 50%. Another widely applied mid-IR method for the selection of Compton-thick AGN ) relies on low X-ray to IR ratios.…”
Section: Discussionmentioning
confidence: 99%